Pengaruh Gender Diversity, Prudence Accounting,Tanggung Jawab Sosial Lingkungan terhadap Manajemen Laba yang Dimoderasi oleh Profitabilitas - Pipit Dwi Cahya Kirana; Vinola Herawaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of the current era of globalization has given rise to various unexpected negative impacts, including Profit Management. Earnings management is an action business managers take to manipulate the information in financial reports for personal gain. This research aims to determine the influence of Gender Diversity, Prudence Accounting and Environmental Social Responsibility on Profit Management with profitability as a moderating variable. The research objects used in this research are State-Owned Enterprises (BUMN) in Indonesia, listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. The number of samples used in the research was 120 data samples. The results of this research indicate that Gender Diversity and Prudence Accounting do not significantly affect Profit Management. Meanwhile, Environmental Social Responsibility has a significant influence on Profit Management in State-Owned Enterprises (BUMN) in Indonesia listed on the Indonesian Stock Exchange in 2019 - 2023